The status quo of short videos as a source of health information regarding bowel preparation before colonoscopy - Liao, Foqiang; Huang, Yunfeng; Lai, Yongkang; Xie, Junfeng (Frontiers in Public Health, 2024)
Background For high-quality colonoscopies, adequate bowel preparation is a prerequisite, closely associated with the diagnostic accuracy and therapeutic safety of colonoscopy. Although popular-science short videos can help people quickly access health information, the overall quality of such short videos as a source of health information regarding bowel preparation before colonoscopy is unclear. Therefore, we intend to conduct a cross-sectional study to investigate the quality of bowel preparation information before colonoscopy through short videos taken on TikTok and Bilibili. Methods The Chinese phrases “colonoscopy” and “bowel preparation” were used as keywords to search for and screen the top 100 videos in the comprehensive rankings on TikTok and Bilibili. The Global Quality Score (GQS) and the modified DISCERN score were used to assess the quality of the information provided in these short videos. Results A total of 186 short videos were included in this study; 56.5% of them were posted by health professionals, whereas 43.5% of them were posted by nonhealth professionals. The overall quality of these videos was unsatisfactory, with a median DISCERN score of 3 (2–4) and a median GQS of 3 (3–4). The radar maps showed that videos posted by gastroenterologists had higher completeness scores regarding outcomes, management, and risk factors, while nongastroenterologists had higher completeness scores concerning adverse effects, symptoms, and definitions of bowel preparation. Additionally, the median DISCERN score and GQS of the videos posted by gastroenterologists were 3 (3–4) and 3 (3–4), respectively, whereas the quality of the videos posted by patients was the worst, with a median DISCERN score of 2 (1–2) and a median GQS of 2 (1.25–3). Conclusion In conclusion, the overall quality of health information-related videos on bowel preparation before colonoscopy posted on specified short video platforms was not satisfactory. Gastroenterologists provide more information on the outcomes, management, and risk factors for bowel preparation before colonoscopy, while nongastroenterologists focus on adverse effects, symptoms, and definitions of bowel preparation.